Muhammadiyah Australia College: Antara Internasionalisasi dan Multitrack Diplomacy: ANTARA INTERNASIONALISASI DAN MULTITRACK DIPLOMACY - Agus Saefurohman (Jisiera: The Journal of Islamic Studies and International Relations, 2023)
This study aims to determine the diplomacy efforts carried out by Muhammadiyah in Australia by analyzing the Multi-track Diplomacy carried out in the internationalization process of Muhammadiyah through Muhammadiyah Australia College (MAC). Using a qualitative descriptive approach, this study tries to uncover the phenomena behind reality and draw conclusions based on data and information collected using collection techniques sourced from books, journals, reports, and news coverage in the media. The results of the study show that the internationalization carried out by Muhammadiyah in Australia has a strong correlation with multitrack diplomacy, as a strategy implemented to establish MAC. At least four of the nine tracks are used: Track Two (NGOs), Track Four (Society and community), Track Five (Education) and Track Seven (Religion). As an NGO-FBO, Muhammadiyah has succeeded in interacting with several related formal authorities in Australia from the city to the state level, having dialogues with the multicultural Australian community, collaborating on the Australian and Muhammadiyah curriculum, and contributing positively to the development of Islam in Australia.